Identification of a Novel Distal Control Region Upstream of the Human Steroidogenic Acute Regulatory Protein (StAR) Gene That Participates in SF-1-dependent Chromatin Architecture - Mizutani, Tetsuya; Yazawa, Takashi; Ju, Yunfeng; Imamichi, Yoshitaka; Uesaka, Miki; Inaoka, Yoshihiko; Matsuura, Kaoru; Kamiki, Yasue; Oki, Masaya; Umezawa, Akihiro; Miyamoto, Kaoru (The Journal of biological chemistry, 2010)
StAR (steroidogenic acute regulatory protein) mediates the transport of cholesterol from the outer to the inner mitochondrial membrane, the process of which is the rate-limiting step for steroidogenesis. Transcriptional regulation of the proximal promoter of the human StAR gene has been well characterized, whereas analysis of its distal control region has not. Recently, we found that SF-1 (steroidogenic factor 1) induced the differentiation of mesenchymal stem cells (MSCs) into steroidogenic cells with the concomitant strong induction of StAR expression. Here, we show, using differentiated MSCs, that StAR expression is regulated by a novel distal control region. Using electrophoretic mobility shift (EMSA) and chromatin immunoprecipitation (ChIP) assays, we identified novel SF-1 binding sites between 3,000 and 3,400 bp upstream of StAR. A luciferase reporter assay revealed that the region worked as a strong regulator to exert maximal transcription of StAR. ChIP analysis of histone H3 revealed that upon SF-1 expression, nucleosome eviction took place at the SF-1 binding sites, not only in the promoter but also in the distal SF-1 binding sites. Chromosome conformation capture analysis revealed that the region upstream of StAR formed a chromatin loop both in the differentiated MSCs and in KGN cells, a human granulosa cell tumor cell line, where SF-1 is endogenously expressed. Finally, SF-1 knockdown resulted in disrupted formation of this chromatin loop in KGN cells. These results indicate that the novel distal control region participate in StAR activation through SF-1 dependent alterations of chromatin structure, including histone eviction and chromatin loop formation.